Generational and Socio-Cultural Effects on Algorithmic Mastery in Denpasar Creative Industry Actors - Mahadhika Feryo Gotama; Nyoman Sri Subawa (Journal of Business Management and Economic Development, 2026)
This study analyzes the influence of demographic and socio-cultural characteristics on social media algorithm understanding among creative industry actors in the Visual Communication Design (VCD) subsector in Denpasar City. Using a quantitative survey approach with 107 respondents selected via purposive sampling from a population of 342 individuals, the study employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) for data analysis. Four independent variables were examined: Generational Cohort (X1), Social Lifestyle (X2), Digital Lifestyle (X3), and Socio-Cultural Environmental Factors (X4), with Social Media Algorithm Mastery (Y) as the dependent variable. Results indicate that the model explains 76.2% of the variance in algorithm mastery (Adjusted R² = 0.762). Hypothesis testing revealed that Digital Lifestyle (t = 2.780; p = 0.005) and Socio-Cultural Environmental Factors (t = 3.342; p = 0.001) have positive and significant effects on Social Media Algorithm Mastery, while Generational Cohort (t = 2.687; p = 0.007) shows a negative and significant effect. Social Lifestyle, however, did not show a significant effect (t = 1.445; p = 0.149). These findings suggest that generational differences, digital activity intensity, and a supportive socio-cultural environment are key determinants of algorithmic mastery among creative entrepreneurs, providing both theoretical contributions to the digital marketing literature and practical implications for enhancing digital capacity in the creative industry sector. This study contributes to the creative economy and digital business literature by demonstrating that socio-cultural environment and digital lifestyle are important determinants of algorithmic capability among creative entrepreneurs in emerging urban economies.